Carbon Nanotubes and Other Engineered Nanoparticles Induced Pathophysiology on Mesothelial Cells and Mesothelial Membranes - Sinis, Sotirios I.; Hatzoglou, Chrissi; Gourgoulianis, Konstantinos I.; Zarogiannis, Sotirios G. (Frontiers in Physiology, 2018)
Nanoparticles have great potential for numerous applications due to their unique physicochemical properties. However, concerns have been raised that they may induce deleterious effects on biological systems. There is accumulating evidence that, like asbestos, inhaled nanomaterials of >5 μm and high aspect ratio (3:1), particularly rod-like carbon nanotubes, may inflict pleural disease including mesothelioma. Additionally, a recent set of case reports suggests that inhalation of polyacrylate/nanosilica could in part be associated with inflammation and fibrosis of the pleura of factory workers. However, the adverse outcomes of nanoparticle exposure to mesothelial tissues are still largely unexplored. In that context, the present review aims to provide an overview of the relevant pathophysiological implications involving toxicological studies describing effects of engineered nanoparticles on mesothelial cells and membranes. In vitro studies primarily emphasize on simulating cellular uptake and toxicity of nanotubes on benign or malignant cell lines. On the other hand, in vivo studies focus on illustrating endpoints of serosal pathology in rodent animal models. From a molecular aspect, some nanoparticle categories are shown to be cytotoxic and genotoxic after acute treatment, whereas chronic incubation may lead to malignant-like transformation. At an organism level, a number of fibrous shaped nanotubes are related with features of chronic inflammation and MWCNT-7 is the only type to consistently inflict mesothelioma.